Surgical treatment of aortic root abscess: 10-year single center experience - S. T. Enginoev; A. A. Zenkov; G. M. Magomedov; U. K. Abdulmejidova; M. A. Guliyev; I. I. Chernov; E. Yu. Gubareva (Российский кардиологический журнал)
The issue of optimal surgical scope in patients with aortic root abscess due to infective endocarditis remains open, since there are different strategies and interventional methods. In addition, the guidelines do not give preference to any particular type of surgical intervention and recommend an individual approach to each situation. The study included 25 patients with aortic root abscess due to aortic valve infective endocarditis. The most frequently performed surgical intervention in patients was the Ross procedure (n=12, 48%). Eight (32%) patients of the center underwent aortic homograft root replacement. Combined surgery was performed in 7 (28%) patients as follows: 3 (12%) patients — interventions on the mitral valve (all patients underwent mitral valve repair due to mitral valve involvement in abscess), 3 (12%) — coronary artery bypass grafting, 1 (4%) — ascending aortic replacement due to dilatation. Five- and ten-year survival after surgical treatment of patients with aortic root abscess was 86,9% and 78,6%, respectively. There was no reintervention and recurrence of infective endocarditis in the long-term period.